Factors Associated with Treatment Compliance in Clients with Mental Disorders: A Cross-sectional Study - Novitasari, Novitasari; Fitri, Nurwijaya; Mardiana, Nova (Inspirasi Foundation, 2025)
Introduction: Mental disorders remain a significant public health issue with increasing prevalence globally and in Indonesia. Non-compliance with treatment and follow-up among clients is often influenced by limited knowledge, lack of family involvement, and inadequate environmental support, which may hinder recovery and increase relapse risk. Objective: Mental disorders are a person's behavior about their mental health condition. Everyone has a different view of behavior in mental health cases, namely a person's emotional, psychological, and emotional stability. The purpose of this study was to determine the relationship between knowledge, family support and environmental support on control compliance in clients with mental disorders in the mental health polyclinic of Depati Bahrin Sungailiat Hospital in 2025. Method: The design in this study used cross-sectional with independent variables (knowledge, family support and environmental support) and dependent variables (control compliance). The population size in this study was 118 people and a sample of 60 people calculated using simple random sampling. The time of the study was May 6, 2025. Result: The results of the study using the Chi Square statistical test obtained a p-value for the knowledge variable 0.000 <0.05, family support 0.014 <0.05 and environmental support 0.000 <0.05. This shows that there is a significant relationship between knowledge, family support and environmental support on control compliance in clients with mental disorders in the mental health polyclinic of Depati Bahrin Sungailiat Hospital in 2025. Conclusion: Suggestions in this study are expected to be used as a source of reference and provide ideas for nursing students when practicing in the field so that students know the factors that can influence control compliance of clients with mental disorders.